PENGARUH DIKLAT FUNGSIONAL, KOMPETENSI SDM DAN MOTIVASI TERHADAP PENGEMBANGAN KARIER KARYAWAN BAGIAN MARKETING PADA BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) BHAKTI SUMEKAR SUMENEP - jurnalmap map; Endang Soekowati; Wasis Budiarto; Indra Prasetyo (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This research was conducted at the ShariÔÇÖa People's Financing Bank (BPRS) Bhakti Sumekar Sumenep with a total sample of 50 people. To analyze which variables between functional training, HR competency, and motivation have a dominant and significant effect on the career development of employees of the marketing department of the Islamic People's Financing Bank (BPRS) Bhakti Sumekar Sumenep. Analysis of data using SPSS, this type of research is explanatory research using quantitative research approaches. The results showed that: 1) Simultaneously functional training, HR competency and motivation had a significant influence on the career development of marketing division employees at the Islamic People's Financing Bank (BPRS) Bhakti Sumekar Sumenep. 2) Partially functional training, HR competency and motivation have a significant influence on the career development of marketing division employees at the Syariah Community Financing Bank (BPRS) Bhakti Sumekar Sumenep. Keywords: Functional Training (X1), HR Competencies (X2), Motivation (X3), And Career Development (Y)